Volumetric and dosimetric comparison of computerised radiotherapy treatment plan between using positron emission tomography/computed tomography (PET/CT) and CT images for target delineation in non-small cell lung cancer patients. Issue 2 (18th April 2016) - Sangudsup, Sanphat; Kaewchur, Tawika; Teeyasoontranon, Waralee; Klunklin, Pitchayaponne; Chawapun, Nisa; Ua-apisitwong, Supoj
Abstract: Purpose: To compare intensity-modulated radiation therapy (IMRT) treatment planning between using positron emission tomography/computed tomography (PET/CT) and CT for target volume delineation in patients with non-small cell lung cancer (NSCLC). Methods: Nine NSCLC patients with PET/CT images were enrolled into this study. Gross tumour volumes (GTVs) were delineated by the PET visual assessment (PETvis), the automated PET (PETauto), standardised uptake value (SUV)>2·5 (PET2·5) and threshold 40% SUVmax (PET40), and CT-based method. For each patient, two IMRT treatment plans based on CT and PET/CT delineation were performed. The target coverage and the dose–volume parameters for organs at risk were analysed. Results: The PETauto referred to PET40 when SUVmax<7 and PET2·5 when SUVmax≥7. The mean GTVs were 15·04, 15·7 and 15·14 cc for PETauto, PETvis and CT based, respectively. The GTV of PETauto was not different from PETvis ( p =0·441) and CT based ( p =0·594). Based on CT delineation in IMRT planning, only 34% of the cases had sufficient PET/CT planning target volumes coverage, whereas the organs at risk dose parameters were not statistically significant ( p >0·05). Conclusions: PET/CT enables more accurate assessment of tumour delineation for NSCLC, therefore improve target coverage in IMRT plan.